Persentase Serangan Lalat Buah pada Tanaman Cabai (Capsicum annum L.) - M Asdhyshani; Ardhansyah Pradana Maulana Latif; Dwi Rahayu Putri Sianipar; Erdi Mefiyanto; Putri Gina; Harman Hamidson (Seminar Nasional Lahan Suboptimal, 2021)
Asdhyshani M, Latif APM, Sianipar DRP, Mefiyanto E, Gina P, Hamidson H. 2021. Percentage of fruitfly attacks on chili plants (Capsicum annum L.). In: Herlinda S et al. (Eds.), Prosiding  Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 747-754. Palembang: Penerbit dan Percetakan Universitas  Sriwijaya (UNSRI).Fruitfly were the most detrimental pests in plant cultivation in Indonesia so that fruitfly were the main pests of horticultural crops, one of which was chili plants.  This observation aimed to determine the percentage of fruitfly attacks on chili (Capsicum annum L. ) plants.  The percentage of attacks was carried out by calculating the amount of plant damage used a formula to found out how much damage to chili plants. For the researched method used a literature studied.  From the results of the studied, it was found that chili plants was attacked by Bactrocera carambolae and Bactrocera papayae.  The percentage of fruitfly attacks on chili was calculated used the following formula; p (percentage of fruitfly attacks) = ???? (number of large chilies infested) divided by ???? (number of large chilies infested) plus ???? (number of healthy chilies) multiplied by 100 percent. In Pancasari village, Sukasada, Buleleng, the highest percentage of attacks was in the AVPP 1003-B line with a percentage of 66.49% and the lowest attacked was in the Kencana variety with a percentage of 23.82%. While in the Dusun Sandan area, Bangli village, Baturiti district, Tabanan regency, the highest percentage of attacks was in the AVPP 1004 line with a percentage of 31.02% and the lowest percentage was in the local variety Kencana, namely 4.12 %. The conclusion is that the largest attack between the two areas are in Pancasari village, Sukasada, Buleleng, in the AVPP 1003-B line with a percentage of 66.49%. And the lowest attack is in Sandan hamlet, Bangli village, Baturiti district, Tabanan regency on the Kencana local variety, which was 4.12 %.